METAVERSE: A STUDY OF CONSUMER PERSPETIVE IN MACAU - Chan, Vanda Cardoso (University of Saint Joseph, 2023)
Technology is an essential and valuable tool nowadays. New technology and innovations are introduced to the public day by day. Metaverse will be a new trend, as the Macau government has been trying to promote this technology since the COVID-19 pandemic is still here. Before this technology goes deeply to the public, this paper attempts to examine the consumer’s perspective of Metaverse and understand the cognition of Macau people about Metaverse. And bring out what factors and conditions will make them accept this technology. A qualitative research method will address the questions and problem to understand consumer perspectives towards this technology. Entrepreneurs, managers, and professionals will be invited to take part in this research. Ten interviews will be carried out in this research for data analysis, which may provide a board overview of this technology in Macau and give recommendations to local entrepreneurs. In conclusion, consumers think it is still not a well-developed technology and is not globally used at this stage. In contrast, if this technology is ready-to-use, it will be a helpful assistant in their businesses. They expect the metaverse to be fully developed in ten or more years
Keywords: Consumer perspective; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; augmented reality; extended reality; marketing strategy; virtual reality

ONLINE IMPULSE BUYING BEHAVIOR: A STUDY OF MACAU CONSUMERS - Cheong, I. Lam (University of Saint Joseph, 2023)
Due to the expansion of the Internet and advancements in technology, e-commerce has been frequently and widely used nowadays. The popularity of online shopping continues to develop and become increasingly common, yet, the concept of impulsive buying has consistently drawn significant attention over the years. In order to fit into the current shopping trend, recognizing the needs and wants of online shoppers as well as providing appropriate approaches are essential tasks for companies to achieve. The question of how to attract consumers to make purchases has been a concern for a long time, and in fact, it is necessary to explore consumers’ online purchase decisions in relation to their impulse buying behavior. In accordance with current academic knowledge, the main objective of this study is to investigate factors that influence consumers' online impulsive buying behavior based on external stimuli (such as sales promotions and websites characteristics) and the elements of marketing mix strategy (product, price, place, and promotion). According to the analysis, the promotion strategy has been identified as the most significant influence on consumers’ decision to make an online impulsive purchase. Therefore, the findings from this study are beneficial for companies and marketers to build a framework in order to develop suitable and effective strategies in order to encourage and stimulate consumers' desire for purchases. Furthermore, the research applies the qualitative methodology by conducting semi-structured interviews with 11 consumers who have previously experienced an online impulse buying
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; e-commerce; external stimuli; marketing mix strategy; online impulse buying; online shopping

Perception on occupational stress in the Hospitality Industry in Macau - Lam Chi Ieng (University of Saint Joseph, 2023)
Employees in the hospitality industry, in particular, face difficult conditions such as overwork, job security, understaffing, and work-life imbalance in today's fast-paced society. Because of that, employees in the hospitality industry experience high levels of occupational stress. Severe conditions of occupational stress may not only lead to health issues for the employee but also affect their work performance. In order to get a better grasp of how occupational stress affects the employees in the hospitality industry in Macau, the research questions are: 1) What are the sources of stress in the Macau hospitality industry? 2) How does the COVID-19 pandemic change the perception of occupational stress among employees in the Macau hospitality industry? How do the companies help the employees in the Macau hospitality industry cope with occupational stress? have been formulated. Semi-structured interviews were conducted with eleven participants working in the hospitality industry, with a median age of 39 years and a median range of 13 years. Based on these interviews, participants expressed their perceptions of occupational stress under the categories of distress and eustress, while coding schemes were applied to all semi-structured interviews. The results on distress showed that reactions from employees and their working conditions, in particular, were the two most important determinants of occupational stress, while motivation helped people grow and develop their confidence. For the changes in occupational stress due to the pandemic, mental reactions from employees were the most significant determinant of occupational stress in the Macau hospitality industry during the changes brought about by the pandemic in these years, closely followed by employee job insecurity. In order to cope with occupational stress, employees should take responsibility for coping with their stress, but employers also have a role to play in this process, like providing good communications and proactive assistance to the employees. Finally, employees' responses were described as more negative as a result of their experience. Further research could focus on more methods for employees to cope with occupational stress in both physical and mental ways
Keywords: Stress; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; hospitality industry; occupational stress; stress management interventions

Management in Macao: global, regional, local forces and critical challenges - Lampo, Alessandro (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Investigating the influence of Instagram on the local foodservice sector in Macau: A Consumers' Perspective - Mac, Hoi Kuan (University of Saint Joseph, 2023)
Nowadays marketers and practitioners recognize the importance of social marketing as a strategy to acquire customers. Accordingly, the enterprises and brands are embracing the use of social network in communicating with potential consumers ad actual consumers, in order its performance so as to increase its sales. Among all those social media platforms, Instagram is one of the platforms which is image orientated and can easily connect with users and provide information with photos and images. As Macau is small‐sized city where there are abundant small to medium‐sized enterprises, the local small firms are switching their marketing strategies by utilizing the Instagram to promote their product online. In order to get a better grasp of how Instagram affects the promotion of the food and beverage product in Macau, the research question has been formulated: “To what extend can the local food sectors in Macau use Instagram as a marketing tool to engage purchasing intention and strengthen their brand equity? From the perspective of customers.” Semi‐structured interviews were conducted with 13 participants who are the Instagram users, with diverse situations of engagement on Instagram. According to the interviews, participants expressed that how Instagram can associate effects with arousal and brand equity (brand awareness, brand image, perceived quality and brand loyalty) and formation of purchase intention eventually through the Instagram marketing activities. The results showed that Instagram marketing activities strongly correlated the brand equity (brand awareness, brand image, and perceived quality while which in turn led to purchasing intention towards the brand. This research comprehensively illustrates the influences of Instagram marketing activities on customer‐based brand equity. The findings of this study will enable local food brands to more accurately forecast the future purchasing behaviors of their customers through Instagram marketing activities and provide a guide in managing brand equity as well
Keywords: Brand Equity; Instagram; Purchase Intention; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on User Acceptance on Customer Behavior for Online Payment in Macau: MPAY Case Study - Wong, Chi Cheng (University of Saint Joseph, 2023)
With the rapid expansion of mobile e-commerce, an increasing number of businesses have jumped into the fray in all facets of the mobile electric commerce industry chain. The payment link is the most competitive. From the norm in the sector to the consumer market, telecom operator rivalry, as well as third-party payment between different companies, never ceases. In the context of mobile e-commerce, however, competition has shifted from traditional product-centered to customer- centered, and business success frequently rests on the customer. As a result, the competition in the mobile e-commerce payment industry is essentially about competing for users. Mpay is characteristic of mobile e-commerce payment firm representatives; on the basis of theoretical analysis, combined with the reality of the economic background, the study chose Mpay mobile payment users as research subjects and analyzed the major variables of user acceptability. The model was built on the basis of an extensive evaluation of past research results of user acceptance model and reference to UTAUT model. The model considered performance expectancy, effort expectancy, and social influence, facilitating condition as independent variables determining user behavior intention, Based on the conceptual model, the paper conducted an empirical investigation as a case study of a Mpay mobile payment user using data from a questionnaire, while also conducting a separate discussion of the impact of perceived risk and trust on user acceptance. The empirical results indicate that for mobile payment users, performance expectancy has the greatest positive effect on behavior intention, while facilitating conditions, social influence, perceived risk, effort expectancy, and trust have no effect. In addition, gender and age were discovered to influence user acceptance
Keywords: Online mobile payment; SmartPLS; Thesis and Dissertations Master of Business Administration (MBA); UTAUT model; University of Saint Joseph; user acceptance

Perception About Challenges and Opportunities of Social Enterprise in Macau - Wong, Chong Chio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Evaluating the Acceptance of Portuguese Residents Towards Chinese Electric Vehicles: the Role of the Country-of-Origin Effect - Xian, Si Tong (University of Saint Joseph, 2023)
This study identifies Portuguese residents’ behavioural intention towards Chinese electric vehicles from the perspective of the Country-of-Origin Effect (COE) and uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) as a guide to design interview questions. According to the existing literature, UTAUT-2, a comprehensive technology acceptance model, has not been used to assess the Portuguese electric vehicle market, and no relevant research has been found to apply the method of combining the COE into the UTAUT-2 framework. The purpose of this study is exploratory in nature, it uses qualitative methods to identify the behavioural intention of Portuguese residents towards the acceptance of Chinese electric vehicles. Data from 16 Portuguese residents was collected through semi-structured interviews and analyzed with qualitative methodology. The study found that factors such as performance expectations, environmental concerns, effort expectations, hedonic motivation, and social influence have a positive impact on Portuguese residents' purchase of electric vehicles, while price value, habits, and convenience conditions have a neutral or negative impact. Regarding COE, apart from social influence, it has no impact on other factors. To increase the popularity and sales of Chinese electric vehicles in Portugal, it is recommended that advertising and marketing efforts focus on price, charging services, after-sales service, and design
Keywords: Consumer Behavior; Country of Origin Effect; Electric Vehicles; Environmental Awareness; Portugal; Sustainability; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph